Inovasi Mahasiswa Kukerta UNRI 2022 Dalam Pencegahan Stunting di Wilayah Kampung KB RW 08 Kelurahan Tangkerang Barat - Auradian Marta; Crisnova Genesia Purba; Mutiara Cahyani Putri; Nora Saulina; Nabila Putri Elvina; Nanda Maulina; Putri Permai; Rafli Nur Ikhsan; Riyanto Amsrof Ramadhan; Sonia Safira; Wahyu Imam Gusnedi (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2022)
The purpose of this journal is to provide broader knowledge related to health development and quality human resources which are related to innovation in stunting prevention in the Tangkerang Barat sub-district by paying attention to existing aspects. Stunting is malnutrition in infants in the first 1000 days of life that lasts a long time and causes delays in brain development and child development, Stunting can also occur before birth and is caused by very poor nutritional intake during pregnancy, poor food quality in line with the frequency of infectious diseases thus inhibiting growth. in the form of stunting prevention, activities carried out by Kukerta students at the University of Riau include collecting data related to stunting in collaboration with the BKKBN and the head of posyandu cadres, socializing stunting to people who attend immunization activities at Posyandu under five, then students carry out processing related to PMT (supplementary feeding), in the form of corn chicken soup, after that the students also made a video which was uploaded to youtube related to the processing stage of this corn chicken soup so that it could be a reference and finally the Kukerta students created an innovation in making biopori holes that promote sanitation for environmental-based stunting prevention together with the Tangkerang village head West and the cadres of the Astra International Tbk.Keywords: Stunting, prevention, innovation, Education